Reinterpretasi Kesaksian Perempuan dalam Qs. Al-Baqarah [2]: 282 (Menelisik Antara Pemahaman Normatif-Tekstualis dan Historis-Kontekstualis) - Wendi Parwanto; Ridwan Rosdiawan (Raheema, 2018)
The polemics on comprehending the position of women as witness within the context of qs. Al-Baqarah [2] : 282 become one of interest to be examined further. Literally, the verse appears to undermine the women status and raises the issue of gender inequality. The article offers an alternate way to look up this widely discussed theme. Using Fazlur Rahman's theory of double movement, namely micro and macro asbab an-nuzul, the verse is revisited in order to gain a more progressive and comprehensive understanding on the status of women witness. Other analytical tools such as linguistics, intra-textuality and inter-textuality are also deployed in enriching the discussion.